PERBANDINGAN ISTILAH KEKERABATAN DALAM BAHASA SASAK DAN MBOJO: KAJIAN ANTROPOLINGUISTIK - Haer, Zuriatin; Fathurrahman; Rizki, Imam; Saharudin (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2025)
This research aims to compare kinship terms in Sasak and Mbojo languages ​​in an anthropolinguistic perspective. The scope of the research includes analyzing the form, function, and meaning of kinship terms used in Sasak and Mbojo language-speaking communities, as well as how social factors such as age, gender, and family relationships influence the use of these terms. This type of research is qualitative descriptive research. The method of data provision in this research is the observation method with the technique of listening to conversation and recording techniques. The research data studied include vocabulary and patterns of kinship greetings from blood relations and marriage relations in Sasak and Mbojo languages. The results of this research is that there are seven levels of kinship terms related to blood relations in the Sasak tribe, while in Mbojo tribe it only reaches the sixth level. In addition, there is a patrilineal system in naming kinship in the Sasak language, such as in the mention of papuq dade ‘grandparents from the father’s line’ and papuq bungkak ‘grandparents from mother’s line’. The naming means that when two people who are still related marry, the grandparents from the male side have more rights over their grandchildren regarding lineage. The child will also follow the greeting or kinship language of the father’s lineage or the lineage of the male family.